The Role of Law in Protecting Society from Human Organ Trafficking Cases in Indonesia. - Hilda Novyana (Universitas Syiah Kuala, 2023)
Human Organs Trafficking is a series of acts of transferring or transplanting parts of human organs that are carried out either on their own accord or because of coercion by other parties in order to gain profit. The purpose of establishing the Unitary State of the Republic of Indonesia as set forth in the Preamble to the Preamble to the 1945 Constitution of the Republic of Indonesia is to protect the entire Indonesian nation and all of Indonesia's bloodshed, promote public welfare and educate the nation's life. live, and participate in carrying out world order based on freedom, peace. immortality and justice. social. RI Law No. 36 of 2009 concerning Health regulates prohibitions related to the act of trading human organs for any reason. The sale/purchase of human organs is categorized as a transnational crime by the UN, where UNTOC as an international legal instrument under UN authority against transnational crimes can be said to have not clearly regulated the prohibition. the practice of buying and selling human organs.